Analisis Faktor-faktor yang Mempengaruhi Produksi Padi Sawah pada Daerah Tengah dan Hilir Aliran Sungai Ayung (Studi Kasus Subak Mambal, Kabupaten Badung dan Subak Pagutan, Kota Denpasar) - PRABANDARI, ADE CANDRA; SUDARMA, MADE; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.2, No.3, Juli 2013, 2013)
ABSTRACT Analysis of The Factor Affecting Rice Production in The Central Region and The Downstream Flow of The ayung River (Case Study in Subak Mambal, Badung Regency and Subak Pagutan, City of Denpasar). Subak Mambal and Subak Pagutan are using the river Ayung as irrigated rice fields. Subak Mambal in Badung Regency i s located at mid dlestream and Subak Pagutan in Denpasar city is located at downstream of Ayung river . The Purpose of this study are to determine of the factors that influence the rice production at both of  Subak , knowing  the different of rice production at both of Subak , and determine of irrigation constraints for paddy rice at both of Subak. This research was done by interview 50 respondents in the two Subak . Based on analysis of linear regression showed three variables which are influence on rice production , employee, fertilizer and water, while the other variables are not affected. Analysisi of difference of production between in two subak, showed there is significant different between rice productioan at Subak Mambal and Subak Pagutan , where rice production at Subak Mambal higher than Subak Pagutan . The contraint s of water irrigation at Subak Mambal is clogged of irrigation canals due to the garbage, and for Subak Pagutan are: (1) the damage of system irrigation, (2) pest crab, (3) garbage, (4) silting of rivers. Keyword : rice , production, c onstarain
Keywords: rice; production; constraint